Development and validation of an educational information web page for family members with relatives in the Intensive Care Unit (ICU) - Azura, Abdul Halain; Yoong, Tang Li; Chan, Chong Mei; Noor Airini, Ibrahim; Khatijah Lim, Abdullah * (Elsevier, 2022)
Aim: This paper describes the development and validation of an educational information web page designed for family members who have relatives in the Intensive Care Unit (ICU).